Enhancing the efficiency of turbo units in thermal power plants under conditions of energy system instability - Savoniuk, M. (National Technical University "Kharkiv Polytechnic Institute", 2025)
This paper explores strategies to improve the efficiency of turbo units in thermal power plants during periods of energy system instability. The study considers thermodynamic modeling, real-time diagnostics, and adaptive control solutions. It highlights the importance of increasing operational resilience and responsiveness under rapidly changing grid conditions. Given the increasing instability of power grids in regions such as Ukraine, the topic is especially timely and practically significant.
Keywords: thermal power plant; turbo units; energy instability; efficiency; adaptive control; Ukraine; optimization